Teacher training, coaching and school libraries in rural indigenous Guatemala: A multi-pronged approach to improving reading proficiency - Sarah L. Peller; Amanda M. Marcotte; Ketan; Craig S. Wells; Nancy Press; Maciej Kos (International Journal of Educational Research Open)
Efforts to address persistent intergenerational poverty in the Global South have focused, in part, on improving both access to and quality of schooling for all children, often including teacher training and provision of materials. Child Aid supports literacy development in hundreds of primary schools in indigenous communities in the rural highlands of Guatemala through an innovative and scalable teacher training program. The program works in over 100 schools at a time offering a four-year intervention with a three-pronged approach: workshops; professional instructional coaching; and providing thousands children's literature books to school libraries and classrooms. Child Aid's program is uniquely focused on improving not only basic reading ability, but reading comprehension skill and critical thinking among students. This study examined whether Child Aid's multifaceted but scalable intervention had a positive effect on children's reading comprehension through two large-scale quasi-experimental studies, with the first serving as the initial study and the second serving as a replication study. Hierarchical linear modeling was used to explore differences in reading comprehension gains between two large samples comparing students’ reading comprehension gains in Child Aid schools with those of students in control schools. In both studies, students in Child Aid schools consistently demonstrated significantly greater gains in their reading comprehension skills than students who were not in Child Aid schools. Additionally, we learned students with weaker skills at the start of the year had the greatest gains. These findings will be presented and implications for the Child Aid program and other literacy interventions will be discussed.